Fall-Related Emergency Department Admission: Fall Environment and Settings and Related Injury Patterns in 6357 Patients with Special Emphasis on the Elderly. (1st March 2014) - Pfortmueller, Carmen A.; Kunz, Mirco; Lindner, Gregor; Zisakis, Athanasios; Puig, Stefan; Exadaktylos, Aristomenis K.
Abstract : Principals . Throughout the world, falls are a major public health problem and a socioeconomic burden. Nevertheless there is little knowledge about how the injury types may be related to the aetiology and setting of the fall, especially in the elderly. We have therefore analysed all patients presenting with a fall to our Emergency Department (ED) over the past five years. Methods . Our retrospective data analysis comprised adult patients admitted to our Emergency Department between January 1, 2006, and December 31, 2010, in relation to a fall. Results . Of a total of 6357 patients 78% (n = 4957 ) patients were younger than 75 years. The main setting for falls was patients home (n = 2239, 35.3%). In contrast to the younger patients, the older population was predominantly female (56.3% versus 38.6%; P < 0.0001 ). Older patients were more likely to fall at home and suffer from medical conditions (all P < 0.0001 ). Injuries to the head (P < 0.0001 ) and to the lower extremity (P < 0.019 ) occurred predominantly in the older population. Age was the sole predictor for recurrent falls (OR 1.2, P < 0.0001 ). Conclusion . Falls at home are the main class of falls for all age groups, particularly in the elderly. Fall prevention strategies must therefore target activities of daily living. Even though falls related to sports mostly take place in the younger cohort, a significant percentage of elderly patients present with falls related to sporting activity. Falls due to medical conditions were most likely to result in mild traumatic brain injury.